2013
DOI: 10.2478/pjvs-2013-0089
|View full text |Cite
|
Sign up to set email alerts
|

Combined administration of bacteriocin- -producing, probiotic strain Enterococcus faecium CCM7420 with Eleutherococcus senticosus and their effect in rabbits

Abstract: The effect of Enterococcus faecium CCM7420 (EF) -enterocin-producing and probiotic strain of rabbit origin, Eleutherococcus senticosus extract (ES) and their combination (ES+EF) was determined on selected bacteria in faeces and caecum content, leukocytes phagocytosis, blood biochemistry and growth performance. Ninety-six weaned rabbits were divided into 3 experimental (ES, EF, ES+EF) and control group (CG). The rabbits in the groups ES and EF+ES were fed commercial diet enriched with E. senticosus extract (30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…strains might induce adipocytes differentiation into a cell type capable of generating insulin sensitivity [ 32 ]. The supplementation of rabbits during 21 days with a combination of 109 cfu/mL of Enterococcus faecium CCM7420 and 30 g/kg feed from the bacteriocin extract of Eleutherococcus senticosus showed a significant reduction of fasting blood glucose compared to the controls [ 33 ]. Although, the beneficial effect of different probiotics on blood glucose regulation has been shown by several studies, some of them have found a hyperglycemic effect of certain probiotic strains compared to untreated animals.…”
Section: Resultsmentioning
confidence: 99%
“…strains might induce adipocytes differentiation into a cell type capable of generating insulin sensitivity [ 32 ]. The supplementation of rabbits during 21 days with a combination of 109 cfu/mL of Enterococcus faecium CCM7420 and 30 g/kg feed from the bacteriocin extract of Eleutherococcus senticosus showed a significant reduction of fasting blood glucose compared to the controls [ 33 ]. Although, the beneficial effect of different probiotics on blood glucose regulation has been shown by several studies, some of them have found a hyperglycemic effect of certain probiotic strains compared to untreated animals.…”
Section: Resultsmentioning
confidence: 99%
“…LAB. The previous administration of CCM7420 and AL41 strains in rabbits individually and in combination with Eleutherococus senticosus led to a decrease in CoNS, CoPS, coliforms, clostridiae and pseudomonads (Pogány Simonová et al, 2013b;Lauková et al, 2016). The lower occurrence of E. coli and Clostridium perfringens in probiotic-treated rabbits was also noted by Kritas et al (2008).…”
Section: Resultsmentioning
confidence: 84%
“…Enterococcus faecium EF9a is a bacteriocin-producing strain with probiotic properties isolated from the faeces of the Hungarian Pannon White rabbit breed (Lauková et al, 2019). Because of our previous application of beneficial E. faecium strains (Szabóová et al, 2012;Pogány Simonová et al, 2013b;Lauková et al, 2016) using different breeds in Slovakia, we decided to focus on determining the dietary effects of autochthonous E. faecium EF9a strain on selected parameters. In this study, the in vivo influence of the EF9a strain was tested on the growth performance, bacterial counts in rabbit faeces, caecum and appendix contents, caecal volatile fatty acid content, blood biochemical parameters and phagocytic activity, and the morphometry of the intestinal villi was also documented.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%
“…In this study, seven semipurified substances (enterocins) produced by Enterococcus faecium strains of ruminal, enviromental, and animal origin isolated and characterized in our laboratory were used as follows: Ent EM41 produced by E. faecium EM41 from ostrich (Lauková et al, 2012b); Ent EK13 [A (P)]; EntM produced by environmental strains E. faecium EK13 (CCM7419) and AL41 (CCM8558) (Mareková et al, , 2007Lauková et al, 2012a); Ent 55 produced by E. faecium EF55 from the chicken crop (Strompfová and ; Ent 2019 produced by rabbits E. faecium 2019 (CCM7420) (Pogány Simonová et al, 2013); Ent M3a produced by E. faecium M3a from rabbit meat (Szabóová et al, 2013); and Ent 412 produced by E. faecium EF412 from horses feces (Lauková et al, 2008). They were prepared following the protocols indicated in previous references.…”
Section: Sensitivity Of Methicillin-resistant Strains To Enterocinsmentioning
confidence: 99%